PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. GRACE SOLUTION - Noviyanti; Hikmah, S.E., M.Si. (SCIENTIA JOURNAL, 2022)
In the era of globalization, the level of competition is getting higher so that it becomes a motivation for business people to be able to improve employee performance to be able to compete. Employee performance is the quality of employee work in completing the work that has been given by the company. Things that affect performance are the work environment and work discipline. The purpose of this research is to determine the effect of work environment and work discipline on the performance of employees of PT. Grace Solutions. This research uses quantitative research methods with descriptive research types. The sampling technique uses the Non Probability Sampling method. The data collection technique in this research is the distribution of questionnaires with a sample of 132 respondents who are employees of PT. Grace Solutions. Data analysis with data quality test, classical assumption test, influence test and hypothesis testing. The results of the t test show that the work environment has no significant effect on employee performance and work discipline has a significant effect on employee performance. And the results of the F test show that the work environment and work discipline simultaneously have a significant effect on employee performance.